Hydrogen Effects in Equiatomic CrFeNiMn Alloy Fabricated by Laser Powder Bed Fusion - Xuan Yang; Yuriy Yagodzinskyy; Yanling Ge; Eryang Lu; Joonas Lehtonen; Lauri Kollo; Simo-Pekka Hannula (Metals, 2021)
This study investigates the effects of laser powder bed fusion (LPBF) on the hydrogen uptake of the face-centered cubic (FCC) equiatomic CrFeNiMn multicomponent alloy after cathodic hydrogen charging (HC). Hydrogen desorption was evaluated using thermal desorption spectroscopy (TDS), and microstructural changes after the TDS test were examined. Results reveal that the amount of hydrogen absorbed by LPBF CrFeNiMn alloy was significantly higher than that in pulsed electric current sintered (PECS) CrFeNiMn alloy or in conventional 316L austenitic stainless steel. The observations are ascribed to the differences in the amount of hydrogen absorbed by the multicomponent lattice, dislocation densities, width of segregation range at cell walls created by the rapid cooling in LBPF, and vacancies remaining after cooling to room temperature. A hydrogen-charged LBPF transmission electron microscope (TEM) specimen was also characterized. Stacking faults and cracks along the (111)-planes of austenite were observed. Scanning electron microscopy (SEM) of the surface of the TDS-tested samples also indicated hydrogen-induced cracks and hydrogen-induced submicron pits at the grain boundary inclusions.